2023
DOI: 10.1101/2023.07.19.549613
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The International Weed Genomics Consortium: Community Resources for Weed Genomics Research

Abstract: The International Weed Genomics Consortium is a collaborative group of researchers focused on developing genomic resources for the study of weedy plants. Weeds are attractive systems for basic and applied research due to their impacts on agricultural systems and capacity to swiftly adapt in response to anthropogenic selection pressures. Our goal is to use genomic information to develop sustainable and effective weed control methods and to provide insights about biotic and abiotic stress tolerance to assist cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 197 publications
0
8
0
Order By: Relevance
“…Six additional species are currently sequenced by large sequencing initiatives (Darwin Tree of Life project 13 , i5k 23 , Aqua-FAANG 24 , the International Weed Genome Consortium 25 ) likely resulting in high quality genomes which were not considered in the current analysis (see ESM Table S3). We found that both the available and high-quality genomic resources have unequal coverage among the large taxonomic groupings with vertebrates having the highest total number and percent coverage, followed by plants and invertebrates (Table1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six additional species are currently sequenced by large sequencing initiatives (Darwin Tree of Life project 13 , i5k 23 , Aqua-FAANG 24 , the International Weed Genome Consortium 25 ) likely resulting in high quality genomes which were not considered in the current analysis (see ESM Table S3). We found that both the available and high-quality genomic resources have unequal coverage among the large taxonomic groupings with vertebrates having the highest total number and percent coverage, followed by plants and invertebrates (Table1).…”
Section: Resultsmentioning
confidence: 99%
“…Six additional species are currently sequenced by large sequencing initiatives (Darwin Tree of Life project 13 , i5k 23 , Aqua-FAANG 24 , the International Weed Genome Consortium 25 ) likely resulting in high quality genomes which were not considered in the current analysis (see ESM Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Metabolite identification via LCMS/MS is a crucial next step to determine the metabolic path of the fluroxypyr molecule. Other future studies include genetic mapping of fluroxypyr resistance via test crosses and either Quantitative Trait Loci (QTL) or bulk‐segregant analysis with resistant Flur‐R and susceptible J01‐S, which will provide chromosomal location of resistance gene(s) (Montgomery et al, 2023). Biochemical studies using P450 and GST inhibitors will indicate whether the enhanced fluroxypyr metabolism can be reversed.…”
Section: Future Workmentioning
confidence: 99%
“…Recent reference genomes are now routinely assembled accompanied by HI‐C, facilitating the identification of distal regulatory elements 60 . This approach is being used by the International Weeds Genomics Consortium to assemble the reference genomes from multiple weed species 61 …”
Section: Approaches For Identification Of Regulatory Elements and Cro...mentioning
confidence: 99%
“…60 This approach is being used by the International Weeds Genomics Consortium to assemble the reference genomes from multiple weed species. 61 These approaches have been applied to build cistromes and to characterize chromatin states during different physiological stages and stresses. For example, the cistrome was built for Arabidopsis, where 1812 TFs and their binding sites were characterized.…”
Section: Discovery and Characterization Of Regulatory Elementsmentioning
confidence: 99%